Listening to the future: podcasts and emerging markets sustain Spotify´s leadership - Ramos, Miguel Vaz (2022)
Throughout the Equity Research report, a valuation was performed on Spotify, the number one company in the audio streaming industry. The company is expected to continue its growth path leveraged by expanding its premium and ad-supported business, particularly in the emerging markets, and by the increased monetization of podcasts in its ad-supported segment. It is issued a “Buy” recommendation, with an expected price of€300,2 per share for the end of 2022, translating in a return of 50,4% for the shareholders.